The Multifaceted Nature of Streptococcal Antigen I/II Proteins in Colonization and Disease Pathogenesis - Manzer, Haider S.; Nobbs, Angela H.; Doran, Kelly S. (Frontiers in Microbiology, 2020)
Streptococci are Gram-positive bacteria that belong to the natural microbiota of humans and animals. Certain streptococcal species are known as opportunistic pathogens with the potential to cause severe invasive disease. Antigen I/II (AgI/II) family proteins are sortase anchored cell surface adhesins that are nearly ubiquitous across streptococci and contribute to many streptococcal diseases, including dental caries, respiratory tract infections, and meningitis. They appear to be multifunctional adhesins with affinities to various host substrata, acting to mediate attachment to host surfaces and stimulate immune responses from the colonized host. Here we will review the literature including recent work that has demonstrated the multifaceted nature of AgI/II family proteins, focusing on their overlapping and distinct functions and their important contribution to streptococcal colonization and disease.